Literatur Review : Pengaruh Senam Hamil Terhadap Kualitas Tidur Ibu Hamil Trimester III - Desrinah Harahap; Yuni Yulia; Fauziah H Wada (Jurnal Surya Medika (JSM), 2022)
Pregnancy exercise is an important method to maintain or improve the physical balance of pregnant women and is an exercise therapy given to pregnant women in the third trimester to achieve a fast, easy and safe delivery. Aim: This literature review is to explain non-pharmacological therapy to determine the sleep quality of third-trimester pregnant women. Method: A literature review using the Literature search method on Google Scholar Results: with the keywords "The Effect of Pregnant Exercise on Sleep Quality for Pregnant Women in the Third Trimester" search for Semantic scholar articles with the keywords "Pregnant mother" AND "Pregnancy exercise" AND "Sleep quality" using according to the inclusion criteria. Conclusion: Pregnancy exercise can improve sleep quality for pregnant women in the third trimester, thus causing pregnant women to have good sleep quality. Pregnancy Gymnastics is an alternative to reduce the complaints of pregnant women, which results in a decrease in the duration of sleep.